Functions of author’s commentaries in the manga “Ghost in the Shell” by Shirō Masamune - I. R. Kuryaev (Японские исследования)
The article analyses the role of author’s commentaries, realized in the form of page footnotes, within the framework of a work of fiction. Shirō Masamune’s manga “Ghost in the Shell” is chosen for analysis because here the author forms a special textual situation when commentaries are not the dominant (as it happens, for example, in V. Nabokov’s “Pale Fire”) or equal (as it happens in D. F. Wallace’s “Infinite Jest”) aspect of the text, but an aspect which, realizing its marginal status, strives to perform several functions in the text. Firstly, the author’s commentaries, as a specific para-text, emphasize the status of manga as a book and give the reader an opportunity to choose one of the possible reading options, thus including the reader in the unfolding of the text. Secondly, the space of commentaries becomes a space of manifestation of the author’s presence, who, through the footnotes, creates essays on science and religion, on the interaction between man and technology, and thus seeks to better articulate the main philosophical theses realized through drawing and narrative in “Ghost in the Shell.” Third, the commentaries allow the author to shift the focus from the narrative to the a-narrative aspects of the text, the very space and world in which the action unfolds. Fourthly, the commentaries emphasize the changing role of the author, who turns from an omnipotent demiurge and creator into a chronicler, a reporter, whose task is to record that what is happening, which unfolds according to the laws formulated by the interaction between characters and spaces, spaces and spaces, spaces and things, things and characters. Thus, through the commentaries, a situation is formed in which the diegetic world seems to acquire a conditional autonomy, the ability to exist outside the narrative, which tells about the adventures of Major Kusanagi Motoko and her subordinates. The author’s commentaries thus, through the clarification of illustrations, characters’ actions, and attention to detail, strengthen the base that facilitates the transference of the plot into other media.